Analisis Kadar Kalsium pada Batita Stunting Kota Semarang: Analysis of Calcium Levels in Stunted Toddlers in Semarang City - Rochly, Revinta Nur Aulia; Ari Yuniastuti; Lisdiana; Nugrahaningsih WH (Life Science, 2025)
Calcium (Ca) is a type of micronutrient that is important for children, especially during toddlerhood (children under three years of age), in their growth and development, where if the body lacks Ca, the bone mineralization process will be low and result in low mineralization of the matrix of new bone deposits, affecting the work of osteoblasts. As a result, children's linear growth will be hampered, and there is a risk of stunting. The research objective is to analyze calcium levels in stunted toddlers aged between 6-36 months in Semarang City. This research is an analytical observational study with a cross-sectional research design carried out in Bandarharjo and Tanjungmas sub-districts. The research sample consisted of 20 stunting toddlers and 20 non-stunting (normal) toddlers with an age range of 6-36 months. The independent variable in this study itself is blood calcium levels. The statistical analysis used was the Mann-Whitney U test. The results revealed that Ca levels in stunted toddlers were 9.95 mg/dL, meanwhile for normal toddlers, it is 16.51 mg/dL. Statistically, it shows that calcium levels in stunted toddlers are significantly different from those in normal toddlers (p = 0.000). In conclusion, there is a statistically significant difference in Ca levels between stunted and normal toddlers aged 6–36 months in Semarang City. The findings suggest that Ca status constitutes an important nutritional factor to be addressed in efforts to prevent stunting among toddlers.